Dharar as a Reason for Divorce Lawsuit in Fiqh and Legislation of Some Muslim Countries: Study on Indonesia, Bahrain, Sudan, Qatar, and Morocco - Trigiyatno, Ali; Sutrisno, Sutrisno (Institut Agama Islam Negeri Curup, 2022)
This paper aims to explain dharar as a reason for divorce in the legislation of five Muslim countries, namely Indonesia, Bahrain, Sudan, Qatar, and Morocco. The five countries were chosen with consideration of representing the Sunni Islamic School and one Shia Islamic School. The approach used is a normative approach combined with a comparative method of the law. Primary legal materials are acts and other legislation relevant to the topic of discussion. The results show that the five countries equally provide room for divorce for the wife if she is experiencing dharar, the judge or hakam is obliged to reconcile the two disputing spouses, dharar includes physical and psychological, and the accusation must be proven using evidence generally applicable in procedural law. As for the difference, only Indonesia emphasizes cruelty and physical abuse, while other countries are general. Morocco is the most complete in regulating dharar as a reason for divorce and has several specifics such as violating the marriage agreement which is categorized as dharar. Morocco also regulates compensation due to á¸arar suffered by the wife, while the other four countries do not discuss it in their family law.